Higher BMI reduces mortality in elderly and Stage III colorectal cancer patients: insights from a multicenter cohort study - Qiao, Yihuan; Kang, Boyu; Jiang, Yu; Zhang, Zecheng; Hu, Baoliang; Song, Jiawei; Ma, Hongjiang; Liu, Shuai; Du, Yongtao; Wang, Qi; Guo, Yajie; Qin, Shihao; et al. (Frontiers in Nutrition, 2025)
BackgroundColorectal cancer (CRC) is a major global health concern, with obesity rates rising and an observed obesity paradox where higher body mass index (BMI) is linked to better outcomes in certain patient groups. This study aims to explore how age and tumor stage modify the association between BMI and mortality risk in CRC patients.Materials and methodsThis retrospective cohort study included 4,114 CRC patients who underwent surgery between December 2013 and December 2019. Patients were categorized by BMI, age, and TNM stage. Multivariate Cox regression models and Kaplan-Meier survival analyses were used to assess the impact of BMI on mortality risk, adjusting for potential confounders such as age, sex, and cancer stage.ResultsHigher BMI was associated with lower mortality risk across the study population. Specifically, the protective effect of higher BMI was most pronounced in patients aged 65 and older and in those with Stage III disease. The multivariate Cox regression analysis revealed that each unit increase in BMI was associated with a 7% decrease in mortality risk. The Kaplan-Meier survival analysis showed significant survival benefits for higher BMI in patients aged 65 and older and in Stage III patients.ConclusionsHigher BMI is associated with lower mortality risk in colorectal cancer patients, particularly in those aged 65 and older and those with Stage III disease. These findings highlight the importance of considering BMI, age, and TNM stage jointly in clinical practice for CRC patients.